Part 1
<h3>Answer: 13</h3>
---------------------
Explanation:
We'll replace every copy of x with -3. Then use PEMDAS to simplify.
f(x) = -2x+7
f(-3) = -2(-3)+7
f(-3) = 6+7
f(-3) = 13
===========================================================
Part 2
<h3>Answer: -11</h3>
---------------------
Explanation:
We work backwards in a sense compared to what part 1 did. Instead of finding f(x) based on x, we determine what x must be for a given f(x).
We'll replace f(x) with 29 and solve for x like so
f(x) = -2x+7
29 = -2x+7
-2x+7 = 29
-2x = 29-7
-2x = 22
x = 22/(-2)
x = -11
Note how if you replaced x with -11, we'd get,
f(x) = -2x+7
f(-11) = -2(-11)+7
f(-11) = 22+7
f(-11) = 29
which helps confirm we have the correct answer.
The correct answer is C.) (y|y > -4).
In order to find the range, we look for the possible numbers that y can be. In this case, you'll see the lowest the number goes is -4 and it continues up forever. Therefore, the answer is that y has to be greater than -4.
Answer:
A ) y=-1/2x+2
Step-by-step explanation:
since the equation is y=2x+4 and the points are (-2,3) and the line is perpendicular to that equation
y=-1/2x+b
enter the point (-2,3)
3=1+b
b=2
so
y=-1/2x+2
Answer:
The linear relationship is represented by y = 2x + 3.
Step-by-step explanation:
We are given a y-intercept of an equation as well as a slope:
We can use this information and substitute it into the slope-intercept form equation to get our linear relationship:
In this formula, m is our slope and b is our y-intercept.
Therefore:
Finally, let us substitute these into the equation:
This is our final equation.